CONFLICT MANAGEMENT IN ISLAMIC EDUCATION INSTITUTIONS (CASE STUDY AT THE FACULTY OF TARBIYAH SCIENCES, UIN RADEN MAS SAID SURAKARTA) - REHANIA, MEITA; NADHFIYAH, KAMILATUN; PEMBANGUNAN, HELDY RAMADHAN PUTRA; BISRI, MOH (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2024)
The view of conflict as a natural law still attaches to people's minds. Conflict is inevitable, it can arise from trivial things in the name of opinions, poor communication, and intolerant values. Conflicts should be managed so that they bring benefits to the group and organization. This research aims to deepen the understanding of conflict management in Islamic educational institutions by reviewing conflicts that occur in the Faculty of Tarbiyah Sciences (FIT), State Islamic University (UIN) Raden Mas Said Surakarta, and observing the role of leaders in managing conflicts in the Faculty. This study uses field research methods, with a descriptive qualitative approach, using the interview method as a data collection technique, as well as document studies. Data was collected through an interview with Vice Dean I of the Faculty of Tarbiyah Sciences UIN Raden Mas Said Surakarta as one of the leaders. The results of the study showed; (1) conflict is an impossible reality to avoid, therefore the attitude that can be taken is to face and find a way to solve it; (2) conflicts that occurred at FIT UIN Raden Mas Said Surakarta regarding differences of interest between individuals and groups within the Faculty; (3) to prevent conflicts, campus culture and Educational Operating Standards (SOP) are introduced from the orientation period; (4) the way to deal with conflicts in the Faculty is by uniting and negotiating (compromise), if it is not resolved, then by appealing, namely leaving it to the higher leadership. ABSTRAKPandangan konflik sebagai hukum alam masih melekat di benak masyarakat. Konflik tidak bisa dihindari, bisa muncul dari hal-hal sepele yang mengatasnamakan pendapat, buruknya komunikasi, dan nilai-nilai yang tidak toleran. Konflik harus dikelola sedemikian rupa sehingga membawa manfaat bagi kelompok dan organisasi. Penelitian ini bertujuan untuk memperdalam pemahaman manajemen konflik di lembaga pendidikan Islam dengan mengkaji konflik yang terjadi di Fakultas Ilmu Tarbiyah (FIT), Universitas Islam Negeri (UIN) Raden Mas Said Surakarta, dan mengamati peran pemimpin dalam mengelola konflik di lembaga pendidikan Islam. Fakultas. Penelitian ini menggunakan metode penelitian lapangan, dengan pendekatan deskriptif kualitatif, menggunakan metode wawancara sebagai teknik pengumpulan data, serta studi dokumen. Pengumpulan data dilakukan melalui wawancara dengan Wakil Dekan I Fakultas Ilmu Tarbiyah UIN Raden Mas Said Surakarta selaku salah satu pimpinan. Hasil penelitian menunjukkan; (1) konflik merupakan suatu kenyataan yang mustahil untuk dihindari, oleh karena itu sikap yang dapat diambil adalah menghadapi dan mencari cara untuk menyelesaikannya; (2) konflik yang terjadi di FIT UIN Raden Mas Said Surakarta mengenai perbedaan kepentingan antar individu dan kelompok di lingkungan Fakultas; (3) untuk mencegah konflik, budaya kampus dan Standar Operasional Pendidikan (SOP) diperkenalkan sejak masa orientasi; (4) Cara mengatasi konflik di Fakultas adalah dengan bersatu dan berunding (kompromi), jika tidak terselesaikan maka dengan cara banding yaitu menyerahkan kepada pimpinan yang lebih tinggi.